PENGGUNAAN MODEL DISCOVERY LEARNING PADA MATA PELAJARAN FIKIH UNTUK MENINGKATKAN HASIL BELAJAR DI SMP DARUL ULUM WARU SIDOARJO - Emilia, Rodhotul; Rohmawati, Ulva Badi’; Aziz, Suudin (Universitas Islam Lamongan, 2023)
Discovery learning offers a general concept that is claimed to improve the results of studying jurisprudence. This is because the objectives of learning fiqh align with the concepts of discovery learning. This research uses a qualitative approach with a case study type. The results of this study are changes in students when the teacher applies the discovery learning model. The visible change is that students are more active in finding out, understanding, observing, and trying to construct concepts and can answer questions here as a stimulus—learning changes from teacher-oriented to student-oriented. In learning here, the role of students is more dominant. Learning is also more exciting and challenging, involving cognitive, psychomotor, and affective in students.